Enhancing the Timeliness of Local Government Financial Reporting: An Agency Theory and Compliance Theory Perspective - Wijaya, Nur Rizki; Putri, Ika Swasti; Wiguna, Ratu Aghnia Raffaidy; Widiastutik, Rika Nur (Indonesian Journal of Business, Accounting and Management, 2025)
The Local Government Financial Report (LKPD) is a key component of public financial governance because promoting transparency and accountability in local government. However, delays in LKPD submissions remain a persistent issue. It indicates weaknesses in administrative discipline and technical capacity. This study examines the impact of audit findings, audit opinions, and regional size on the timeliness of LKPD submission by provincial governments in Indonesia from 2019 to 2023. Using a sample of 170 provincial governments, the research applies multiple linear regression analysis in SPSS to assess the relationship between these factors and timeliness. The findings show that favourable audit opinions positively affect timeliness, while audit findings and regional size are negatively associated with timely submissions. Larger regions and those with significant audit findings tend to experience delays in their submissions. The study underscores the importance of favourable audit opinions and highlights the role of structural and technical challenges in causing delays. Agency Theory and Compliance Theory provide frameworks for understanding these dynamics, focusing on external pressures and internal compliance systems. The study concludes by offering recommendations to address persistent delays in LKPD submissions